Prenatal glucocorticoid programming of 11-beta hydroxysteroid dehydrogenase type 2 and erythropoietin in the kidney - Tang, Justin I-Shing (The University of Edinburgh, 2011)
Numerous epidemiological studies show a strong association between low birth weight and later life hypertension and metabolic disease. Excessive in utero exposure to glucocorticoids (‘stress hormones’) has been hypothesized to be important in such developmental ‘programming’, acting via crucial physiological, gene expression or structural changes in the developing fetus. Normally, the fetus is protected from the high levels of maternal glucocorticoids by an enzymic placental barrier, 11 betahydroxysteroid dehydrogenase type 2 (11β-HSD2). In the placenta, 11β-HSD2 efficiently converts active maternal glucocorticoids (cortisol in humans; corticosterone in rodents) to physiologically inactive 11-keto forms. In previous studies in rats, maternal administration of dexamethasone, a synthetic glucocorticoid which is minimally metabolized by 11β-HSD2, or carbenoxolone, a potent inhibitor of 11 β-hydroxysteroid dehydrogenase, increased glucocorticoid load to the fetus. This resulted in lower offspring birthweight and later life hypertension and hyperglycemia — important components of the metabolic syndrome. These programming effects were seen when dexamethasone was administered selectively during the third week of gestation. We have used this well-validated model of programming to dissect the molecular mechanisms that mediate the programming of hypertension. In accord with previous observations, administration of dexamethasone (100μg/kg/day) to pregnant rats during the last week of pregnancy significantly reduced offspring birthweight by 10%. Moreover, the 9 month-old adult offspring had systolic hypertension (9% rise) accompanied by significant hypokalemia (10% fall K+). The coexistence of hypertension and hypokalemia suggested that prenatal overexposure to dexamethasone might increase mineralocorticoid activity in the kidney. Intriguingly, although offspring of dexamethasone-treated dams had 46% lower plasma renin concentrations (consistent with intravascular fluid volume expansion), 24-hour total urinary aldosterone levels were significantly reduced compared to controls (reduction of 56%). Maternal dexamethasone treatment was associated with a permanent decrease in 11β- HSD2 mRNA and activity in the kidney of the offspring (45% and 36% respectively). 11β-HSD2 plays an important role in regulation of renal sodium reabsorption (and thereby blood pressure) by acting as a pre-receptor barrier to MR access, preventing glucocorticoids from activating MR in the distal nephron. Thus, the decrease in renal 11β-HSD2 activity would allow greater endogenous glucocorticoids to activate MR, likely accounting for the low-renin, low-aldosterone hypokalemic hypertensive phenotype observed in these offspring. Other components of mineralocorticoid or glucocorticoid signaling pathways, including mineralocorticoid receptor (MR), glucocorticoid receptor (GR) and 11-beta hydroxysteroid dehydrogenase type 1 (11β-HSD1) were not altered in the offspring kidney by prenatal glucocorticoid exposure. Dexamethasone-programmed offspring also showed exaggerated mineralocorticoid activity with increased kalliuresis in response to exogenously administered corticosterone, suggesting that the decrease in renal 11β-HSD2 is functionally important. In this respect, our rat model resembles the syndrome of apparent mineralocorticoid excess where reduced 11β-HSD2 allows illicit activation of MR by glucocorticoids, resulting in excessive sodium reabsorption, hypertension and hypokalemia. We also studied the effects of maternal dexamethasone on offspring erythropoietin expression in the kidney. This followed from previous observations that identified the hepatocyte nuclear factor 4 alpha (HNF4α) as a key gene up-regulated in dexamethasone-programmed offspring liver, where it might be involved in mediating hyperglycemia. HNF4α is also expressed in the kidney. The role of HNF4α in the kidney is not fully understood, but has been implicated in regulation of erythropoietin synthesis. As in the liver, prenatal exposure to dexamethasone caused a significant increase (64% increase) in renal HNF4α expression. The increase in renal HNF4α mRNA was observed early (in one week old offspring) and persisted into adulthood. This was associated with significantly elevated levels of erythropoietin in circulation (110% increase). Moreover, animals that were exposed to prenatal dexamethasone had significantly increased red blood cell mass (7% increase), presumably as a result of upregulation of erythropoietin.
Keywords: programming; glucocorticoid; 11β-HSD1; 11 Beta Hydroxysteroid Dehydrogenase type 1; hypertension; salt sensitivity; hypokalemia; erythropoietin; rell cell mass; HNF4 alpha kidney